Physicochemical properties, flavor intensity and oxidative stability of different camellia oils - Jiang, Xiaofei; Wu, Shimin; Yuan, Dan; Lamu, Ciji; Wang, Qiang; Zhang, Zhiheng (International Journal of Agricultural and Biological Engineering, 2018)
Comparison and analysis of physicochemical properties and oxidative stability of 10 brands of camellia oils were conducted in this study. Results showed that more attention should be paid to the iodine (IV), saponification (SV) and peroxide (PV) values of camellia oils during sampling inspection as they were more likely to be out the range of quality standards. Regression analysis between physicochemical indices and oxidative stability showed individual index could not affect the stability of camellia oils significantly (p>0.05). However, very high correlations were found between physical indices such as optical rotation (OR) and turbidity (R=–0.929), turbidity and color (R=–0.930). High correlations were found between chemical indices such as IV and moisture and volatile matter (MVM) (R=–0.853), IV and PV (R=0.831), MVM and PV (R=–0.809). Package with nitrogen could retard the oxidation of camellia oil. These results may be useful for rapid evaluation, differentiation and quality improvement of camellia oils. Keywords: camellia oil, optical rotation, regression analysis, quality indices, sensory evaluation DOI: 10.25165/j.ijabe.20181105.3656 Citation: Jiang X F, Wu S M, Yuan D, Lamu C J, Wang Q, Zhang Z H. Physicochemical properties, flavor intensity and oxidative stability of different camellia oils. Int J Agric & Biol Eng, 2018; 11(5): 230–235.